Preparation of silicon-carbon composite material using polycarbosilane and its application

The silicon-carbon precursor is prepared by the liquid silane method and coated with metal-doped amorphous carbon, which solves the problem of poor power performance and cycle performance of silicon-carbon materials in lithium-ion batteries, and realizes the preparation and application of high-performance silicon-carbon composite materials. .

CN118693268BActive Publication Date: 2025-01-24ZHIHUA NEW ENERGY TECH (ZHEJIANG) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411163038.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-24
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The silicon carbon materials used in existing lithium-ion batteries have problems such as power performance deviation, poor circulation performance and poor production consistency, which is difficult to meet the requirements of high energy density and safety.

Method used

The silicon carbon precursor is prepared by the liquid silane method, and its surface is coated with metal-doped amorphous carbon. Polycarbosilane, a basic catalyst and an organic solvent are used for reaction, and then the coating of the material is improved through vacuum vaporization and deposition steps. integrity and electronic conductivity.

Benefits of technology

It significantly improves the power performance, cycle performance and preparation consistency of silicon-carbon composite materials, reduces full power expansion, and improves the electronic conductivity and liquid retention performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118693268B_ABST
    Figure CN118693268B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-ion battery material preparation, and discloses a method for preparing a silicon-carbon composite material using polycarbosilane and its application. Specifically, a polycarbosilane material and an alkaline catalyst are added to an organic solvent, transferred to a high-pressure reactor for reaction, filtered, and carbonized to obtain a silicon-carbon precursor material; then, a metal-doped amorphous carbon gas is used to deposit and coat the silicon-carbon precursor material to obtain a silicon-carbon composite material. The preparation method of the present invention utilizes the low cracking temperature of liquid polycarbosilane, the small silicon grain size, and the simple reaction conditions to reduce the expansion rate of the silicon-carbon material and improve the initial efficiency of the silicon-carbon material; the outer shell is further coated with metal-doped amorphous carbon to reduce the material impedance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery material preparation, in particular to a silicon-carbon composite material prepared by using polycarbosilane and its application. Background Art

[0002] New silicon-carbon materials have become the preferred materials for high-energy-density lithium-ion batteries due to their high specific capacity, low expansion, and high initial efficiency. The main preparation methods are silane gas cracking method and liquid silane deposition cracking method. The silane gas cracking method mainly generates nano-silicon by cracking SiH4 and depositing it in porous carbon, and then passivates or coats its surface to obtain silicon-carbon materials. It has problems such as high safety risks and poor consistency, which makes it difficult to mass-produce the preparation method and its materials. The liquid silane cracking method does not react violently with air, oxygen, and water during the preparation process, and the reaction conditions are not harsh. Its preparation process is simple and easy to industrialize, but the power performance of the materials prepared is biased. Therefore, there is an urgent need to develop an effective method for preparing high-performance silicon-carbon composite materials. Summary of the invention

[0003] In order to improve the power performance and cycle performance of silicon-carbon materials and improve the consistency of products, the present invention prepares a silicon-carbon precursor by a liquid silane method and coats metal-doped amorphous carbon on its surface to obtain a silicon-carbon composite material.

[0004] The first aspect of the present invention provides a new type of silicon-carbon composite material, which is obtained according to the following preparation method: adding a polycarbosilane material and a basic catalyst to an organic solvent, transferring to a high-pressure reactor for reaction, filtering, and carbonizing to obtain a silicon-carbon precursor material; then using a metal-doped amorphous carbon gas to deposit and coat the silicon-carbon precursor material to obtain a silicon-carbon composite material. Wherein, the polycarbosilane material is selected from one or more of polycarbomethylsilane, polydimethylsilane, polyethylsilane, and bis(polyethylene glycol methyl ether)dimethylsilane. Wherein, the basic catalyst is selected from one or more of basic copper carbonate, basic zinc carbonate, basic bismuth carbonate, and zinc carbamate; wherein, the organic solvent is selected from one or more of toluene and xylene.

[0005] A second aspect of the present invention provides a method for preparing a novel silicon-carbon composite material, comprising the following steps:

[0006] Step S1: adding polycarbosilane and alkaline catalyst to an organic solvent according to a mass ratio of polycarbosilane: alkaline catalyst: organic solvent = 100: 1-5: 500-1500, and then transferring to a reactor A, reacting at a temperature of 250-500° C. for 1-6 hours, filtering, and carbonizing the filter residue at a temperature of 700-1100° C. for 1-6 hours to obtain a silicon-carbon precursor material;

[0007] Step S2: Add the organometallic compound to the n-heptane organic solvent to prepare a molar concentration of 0.01-0.05 mol / L, and transfer it to the vacuum reactor B, then evacuate to 0.01-0.1Mpa, and heat to 200-300°C to obtain gasified gas; then pass the gasified gas from the vacuum reactor B into the reactor A at a flow rate of 10-100ml / min, and heat to 500-700°C for deposition for 30-300min to obtain a silicon-carbon composite material.

[0008] Wherein, the polycarbosilane in step S1 is selected from one or more of polycarbomethylsilane, polydimethylsilane, polyethylsilane, and bis(polyethylene glycol methyl ether)dimethylsilane.

[0009] Wherein, the basic catalyst in step S1 is selected from one or more of basic copper carbonate, basic zinc carbonate, basic bismuth carbonate, and zinc carbamate. The organic solvent in step S1 is selected from one or more of toluene and xylene.

[0010] Wherein, the organic metal compound in step S2 is selected from Ni(C5H5)2, Ni(CH3C5H4), Ni(C5H7O2)2, Ni(C 11 H 19 O2)2、Ni(C7H 16 NO), Ni(C7H 17 NO)2.

[0011] A third aspect of the present invention provides a negative electrode plate for a lithium ion battery, comprising a negative electrode current collector and a negative electrode material coated on at least one surface of the negative electrode current collector, wherein the negative electrode material comprises the above-mentioned silicon-carbon composite material.

[0012] A fourth aspect of the present invention provides a lithium ion battery comprising the above-mentioned negative electrode plate, which also includes a positive electrode plate and a separator between the positive electrode plate and the negative electrode plate.

[0013] Beneficial effects of the present invention

[0014] (1) The present invention uses vacuum gasification of polycarbosilane to reduce the cracking temperature, reduce the silicon grain size, and improve the cycle performance; at the same time, the carbon contained in polycarbosilane improves the electronic conductivity of the material; and the organic catalyst can catalyze the polycarbosilane to form a porous structure during the cracking process, reducing its full-charge expansion.

[0015] (2) The present invention generates metal-doped amorphous carbon gas by gasification and cracking of organic metal compounds, and deposits the gas on the surface of the silicon-carbon precursor, thereby improving the coating integrity of the silicon-carbon precursor and improving the electronic conductivity and cycle performance of the material.

[0016] (3) The novel silicon-carbon material prepared by the present invention is applied to the field of lithium-ion batteries and has the characteristics of low expansion, good power performance, and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0018] Figure 1 This is the SEM image of the silicon-carbon material prepared in Example 1. DETAILED DESCRIPTION

[0019] The novel silicon-carbon composite material and its application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0020] Example 1

[0021] A method for preparing a silicon-carbon composite material using polycarbosilane, characterized in that it comprises the following steps:

[0022] Step S1: adding 100 g of polycarbomethylsilane and 3 g of basic copper carbonate to 1000 g of toluene organic solvent, and then transferring to reactor A, reacting at a temperature of 350° C. for 3 h, filtering, and carbonizing the filter residue at a temperature of 900° C. for 3 h to obtain a silicon-carbon precursor material;

[0023] Step S2: Add 5.67 g (0.03 mol) of Ni(C5H5)2 to 1000 L of n-heptane organic solvent to a molar concentration of 0.03 mol / L, and transfer it to a vacuum reactor B. Then, evacuate it to 0.05 MPa and heat it to 250°C to obtain a vaporized gas. Then, pass the vaporized gas from the vacuum reactor B into the reactor A at a flow rate of 50 ml / min, and heat it to 600°C for deposition for 120 min to obtain a silicon-carbon composite material.

[0024] Example 2

[0025] A method for preparing a silicon-carbon composite material using polycarbosilane, characterized in that it comprises the following steps:

[0026] Step S1: adding 100 g of polydimethylsilane and 1 g of basic zinc carbonate to 500 g of xylene organic solvent, and then transferring to reactor A, reacting at a temperature of 250° C. for 6 h, filtering, and carbonizing the filter residue at a temperature of 700° C. for 6 h to obtain a silicon-carbon precursor material;

[0027] Step S2: Add 2.56 g Ni(C5H7O2)2 (0.01 mol) to 1000 ml n-heptane organic solvent to a molar concentration of 0.01 mol / L, and transfer it to a vacuum reactor B, then evacuate to 0.01 MPa, and heat to 200°C to obtain a vaporized gas; then, pass the vaporized gas from the vacuum reactor B into the reactor A at a flow rate of 10 ml / min, and heat to 500°C for deposition for 300 min to obtain a silicon-carbon composite material.

[0028] Example 3

[0029] Step S1: adding 100 g of polyethylsilane and 5 g of basic bismuth carbonate to 1500 g of xylene organic solvent, then transferring to reactor A, reacting at a temperature of 500° C. for 1 h, filtering, and carbonizing the filter residue at a temperature of 1100° C. for 1 h to obtain a silicon-carbon precursor material;

[0030] Step S2: 9.4 g (0.05 mol) Ni(C7H 16 NO) organic metal compound is added to 1000 ml of n-heptane organic solvent to prepare a molar concentration of 0.05 mol / L, and transferred to a vacuum reactor B, then evacuated to 0.1 MPa, and heated to 300°C to obtain a gasified gas; then the gasified gas from the vacuum reactor B is introduced into the reactor A at a flow rate of 100 ml / min, and heated to 700°C for deposition for 30 minutes to obtain a silicon-carbon composite material.

[0031] Comparative Example 1: The difference from Example 1 is that basic copper carbonate is not added, and the other aspects are the same as Example 1.

[0032] Comparative Example 2: The difference from Example 1 is that Ni(C5H5)2 is replaced by phenolic resin, and the rest is the same as Example 1.

[0033] Test Case

[0034] 1. SEM test

[0035] Figure 1 This is a SEM image of the silicon-carbon composite material prepared in Example 1. It can be seen from the image that the material has a granular structure with a particle size between 5-10 μm.

[0036] 2. Physical and chemical performance test:

[0037] The specific surface area of ​​each silicon-carbon composite material was tested with reference to the national standard GB / T 38823-2020 "Silicon Carbon", and the conductivity of each composite material was tested using a four-probe tester. The pore size and pore volume of the silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-2 were also tested respectively; the test results are shown in Table 1 below.

[0038] 3. Button battery test:

[0039] The silicon-carbon composite materials corresponding to Examples 1-3 and Comparative Examples 1-2 were used as negative electrode materials for lithium-ion batteries to prepare button batteries according to the following method:

[0040] A binder, a conductive agent and a solvent are added to each corresponding silicon-carbon composite material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet; the binder used is LA132, the conductive agent is SP (conductive carbon black), the solvent is NMP, and the usage ratio of the composite material, SP, LA132, and NMP is 95g:1g:4g:220mL; the electrolyte is a solution with LiPF6 as the electrolyte, and the concentration is 1mol / L, wherein the solvent is a mixture of EC and DEC in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film.

[0041] Each button cell was assembled in an argon-filled glove box, and then the electrochemical performance was tested. Specifically, the electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester. The charge and discharge voltage range was 0.005V to 2.0V, the charge and discharge rate was 0.1C, and the charging DCR (50% SOC) was tested at the same time. The test results are shown in Table 1 below.

[0042] The negative electrode sheet of the above button battery was also tested for full charge expansion. The specific test process is: the thickness D1 of the negative electrode sheet of the button battery after rolling was tested, and then the full charge thickness D2 of the negative electrode sheet of the button battery was dissected when it was fully charged to 100% SOC, and then the expansion rate was calculated (expansion rate = (D1-D2) / D1*100%); the test results are shown in Table 1 below.

[0043] Table 1

[0044] First discharge specific capacity (mAh / g) First efficiency (%) <![CDATA[Specific surface area (m 2 / g)]]> Charging DCR(Ω) Powder conductivity (S / cm) Full charge expansion Pore ​​size (nm) <![CDATA[Pore volume (cm 3 / g)]]> Example 1 1878.6 92.8 4.1 21.5 10.84 57.4% 5.23 1.89 Example 2 1854.8 91.1 3.7 24.7 9.56 64.2% 5.71 1.24 Example 3 1923.4 93.1 4.5 18.9 12.34 50.5% 5.16 2.06 Comparative Example 1 1702.8 90.1 3.0 34.6 6.78 78.3% 4.47 3.26 Comparative Example 2 1730.4 90.8 3.7 38.8 2.34 89.4% 4.23 3.45

[0045] It can be seen from the data in Table 1 above that the specific capacity and the first efficiency of the silicon-carbon composite materials prepared in Examples 1-3 of the present application are significantly better than those in Comparative Examples 1-2; the reason may be that: vacuum gasification through polycarbosilane has a low cracking temperature, which reduces its silicon grain size. At the same time, polycarbosilane contains carbon to improve the electronic conductivity of the material; and the organic catalyst can catalyze the formation of a porous structure in the cracking process of polycarbosilane, reducing its full-charge expansion.

[0046] 4. Soft pack performance test:

[0047] The silicon-carbon composite materials corresponding to Examples 1-3 and Comparative Examples 1-2 were doped with 90% artificial graphite as negative electrode materials (i.e., negative electrode plates) and positive electrode ternary materials (LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2), electrolyte and separator are assembled into a 5Ah soft-pack battery; wherein the separator is celegard 2400, the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.3 mol / L) to prepare the soft-pack battery.

[0048] The following performance tests are performed on each soft pack battery:

[0049] A. Liquid absorption capacity test: Use a 1mL burette and absorb 1mL of electrolyte, add one drop on the surface of each negative electrode, and time until the electrolyte is completely absorbed. Record the time t. The test results are shown in Table 2 below.

[0050] B. Liquid retention rate test: Calculate the theoretical liquid absorption m1 of the corresponding negative electrode sheet according to the parameters of each negative electrode sheet, and weigh the weight of the negative electrode sheet as m2. Then, soak the negative electrode sheet in the electrolyte for 24 hours, weigh the weight of the negative electrode sheet as m3, and calculate the liquid absorption of the negative electrode sheet as m3-m2, according to the following formula: Liquid retention rate = (m3-m2)*100% / m1; the test results are shown in Table 2 below.

[0051] Table 2

[0052] Liquid suction speed (S) Fluid retention rate Example 1 46 93.1% Example 2 52 92.0% Example 3 40 94.2% Comparative Example 1 74 88.3% Comparative Example 2 65 89.7%

[0053] It can be seen from Table 2 that the liquid absorption and retention capacity of the silicon-carbon composite materials provided in Examples 1-3 is higher than that in Comparative Examples 1-2; the reason may be that the silicon-carbon composite materials provided in the examples of the present application have a larger specific surface area, which can directly improve the liquid absorption and retention capacity of the silicon-carbon composite materials.

[0054] c. Rate and cycle performance test:

[0055] The prepared soft-pack batteries were subjected to cycle performance tests and rate tests; the test conditions for the cycle performance test were as follows: the charge and discharge voltage range was 2.5 to 4.2 V, the temperature was 25 ± 3.0 ° C, the charge and discharge rate was 1.0 C / 1.0 C, and the number of cycles was 500; the test conditions for the rate test were as follows: the constant current ratio of each soft-pack battery under 2C conditions was tested (2C constant current capacity / (2C constant current capacity + 0.1C constant voltage capacity)); the test results are shown in Table 3 below.

[0056] Table 3

[0057] Capacity retention after 500 cycles (%) 2C constant current ratio Example 1 94.2 89.2% Example 2 93.3 88.7% Example 3 94.8 90.4% Comparative Example 1 89.8 86.1% Comparative Example 2 87.3 84.5%

[0058] It can be seen from Table 3 that the rate and cycle performance of the soft-pack lithium-ion batteries prepared using the silicon-carbon composite materials provided in Examples 1-3 are significantly better than those in Comparative Examples 1-2. The reason may be that: the example materials have high powder conductivity, which improves the constant current ratio of the material; at the same time, the example materials have a high specific surface area, which improves the liquid retention performance of the material and improves the cycle performance.

[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that several improvements and modifications may be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention and do not deviate from the scope defined by the claims of the present invention.

Claims

1. A silicon-carbon composite material, characterized in that: It is obtained according to the following preparation method: adding polycarbosilane material and alkaline catalyst to an organic solvent, transferring to a high-pressure reactor A for reaction, filtering, and carbonizing to obtain a silicon-carbon precursor material; then, adding an organic metal compound to an n-heptane organic solvent to prepare a molar concentration of 0.01-0.05 mol / L, and transferring to a vacuum reactor B, and then evacuating to 0.01-0.1 Mpa, and heating to 200-300° C. to obtain a gasified gas; then, passing the gasified gas of the vacuum reactor B into the reactor A at a flow rate of 10-100 ml / min, and heating to 500-700° C. for deposition for 30-300 min to obtain a silicon-carbon composite material; Wherein, the polycarbosilane material is selected from one or more of polycarbomethylsilane, polydimethylsilane, polyethylsilane, and bis(ethylene glycol)methyl ether dimethylsilane; the organic metal compound is selected from Ni(C5H5)2, Ni(CH3C5H4), Ni(C5H7O2)2, Ni(C 11 H 19 O2)2、Ni(C7H 16 NO), Ni(C7H 17 NO)2; the basic catalyst is selected from one or more of basic copper carbonate, basic zinc carbonate, and basic bismuth carbonate; the organic solvent is selected from one or more of toluene and xylene.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The steps include: Step S1: adding polycarbosilane and alkaline catalyst to an organic solvent according to a mass ratio of polycarbosilane: alkaline catalyst: organic solvent = 100: 1-5: 500-1500, and then transferring to a high-pressure reactor A, reacting at a temperature of 250-500° C. for 1-6 hours, filtering, and carbonizing the filter residue at a temperature of 700-1100° C. for 1-6 hours to obtain a silicon-carbon precursor material; Step S2: adding an organometallic compound to an organic solvent of n-heptane to a molar concentration of 0.01-0.05 mol / L, and transferring the compound to a vacuum reactor B, and then evacuating the reactor to 0.01-0.1 Mpa, and heating the reactor to 200-300° C. to obtain a gasified gas; then, passing the gasified gas from the vacuum reactor B into the reactor A at a flow rate of 10-100 ml / min, and heating the gas to 500-700° C. for deposition for 30-300 min to obtain a silicon-carbon composite material; Wherein, the polycarbosilane material is selected from one or more of polycarbomethylsilane, polydimethylsilane, polyethylsilane, and bis(ethylene glycol) methyl ether dimethylsilane; the organic metal compound in step S2 is selected from Ni(C5H5)2, Ni(CH3C5H4), Ni(C5H7O2)2, Ni(C 11 H 19 O2)2、Ni(C7H 16 NO), Ni(C7H 17 NO)2; the basic catalyst is selected from one or more of basic copper carbonate, basic zinc carbonate, and basic bismuth carbonate; the organic solvent is selected from one or more of toluene and xylene.

3. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode material coated on at least one surface of the negative electrode current collector, and the negative electrode material includes the silicon-carbon composite material according to claim 1 or the silicon-carbon composite material prepared according to claim 2.

4. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet is the negative electrode sheet according to claim 3.

Citation Information

Patent Citations

  • Method for preparing silicon-carbon composite material based on silane cracking method and application of silicon-carbon composite material

    CN118117071A

  • Multi-element doped silicon-carbon composite material, preparation method thereof and lithium ion battery

    CN118387879A